Internal versus external focus of attention on high-intensity exercise performance in judo athletes - Kons, R. L.; Detanico, D.; Franchini, E. (Sport Sciences for Health, 2021)
Purpose The aim of this study was to verify the effects of internal and external focus of attention, and a control condition on the performance, physiological and perceptive responses in a judo-specific all-out interval protocols.